Nonperforming loans in Palestinian banks - analysis and treatment - Shaheen, Yasser Ahmed; Shaheen, Rawan Hazem (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the reality and causes of non-performing loans phenomenon in Palestinian banks and proposed mechanisms to address them. The researchers used the descriptive analytical approach, and they built a questionnaire as a study tool in addition to using secondary data published by the Palestinian Monetary Authority during the year 2019, and the study population consisted of (75) banks and branches, the population of the study population reached 450 employees. The study was conducted on a sample consisting of (190) employees and managers of facilities employees and bank managers and their branches, who were chosen in a systematic, stratified, random manner. The results showed that there is an increase in the size and percentage of non-performing loans in the Palestinian banking sector during the study period, and that the most important reasons for faltering loans were related to the borrower himself, ranked first with an arithmetic average (3.74) and a relative weight (74.8%), followed by the causes of default related to the bank itself with an arithmetic average (3.02) and relative weight (60.4%), then the default causes that are outside the borrower’s and the bank’s control with an arithmetic average (2.99) and a relative weight (59.8%), and finally defaulting related to laws, regulations and laws with an average arithmetic (2.97) and relative weight (59.4%), arithmetic mean For the total score of the causes of default reached (3.18), with a percentage of (63.6%). Based on the results, the researchers recommended: the necessity of establishing departments and divisions for dealing with nonperforming loans to ensure the study of the borrower in terms of the type of activity and how to use the loans, not to rely on guarantees only when granting the lending decision, and that he be dependent on the economic feasibility of the project and follow-up.